(untitled) (Journal of Economic Research & Business Administration, 2016)
The article discusses the concept of “superflexibility”and principles of super-flexible companies studied by H.Bahrami and S.Evans during their work in Silicon Valley. Considering the pace and trends of Kazakhstan’s business transformation the article authors concluded that the principles of super-flexible organizational structures can become a methodological ba-sis for managing companies in Kazakhstan that can increase the country’s competitiveness in the future. Companies that adhere to the principles of super-flexible companies will have the ability to quickly and effectively respond to the situation as well as be able to resist the pressure from the external environment.